Encryption and Decryption Techniques in Cloud Computing (International Journal of Innovative Research in Computer Science & Technology, 2021)
While big data applications in cloud  computing are rapidly growing in popularity, privacy  issues have increased dramatically. Encrypting data in real  time is one of the most important issues during data  processing and transfer. In order to reach an acceptable  performance level, many modern applications forego data  encryptions, which is incompatible with privacy concerns.  This article covers several virtualized processes and  analyses the cloud technology safety challenge and way to  solve in brightness of cloud technology ideas and  characteristics. Information confidentiality and  dependability of services are major cybersecurity problems  in internet applications. A singular monitoring platform  will not address the cloud hosting privacy challenge; to  defend the whole clouds infrastructure, a mix of old and  new methods and technology must be employed in  harmony. The author demonstrates the use of encoding and  decoding techniques in aspects of the data confidentiality,  computation time, and virtualized systems effectiveness.  On top of this infrastructure, they may enable dynamically  data storage functions on encoded information sections for  inclusion, deleting, and updating, which we think will be  future work for improvement.
Keywords: Cloud Computing; Data; Encryption; Privacy; Security